Differences and Similarities in Predictors of Externalizing Behavior Problems Between Boys and Girls: A 1-Year Follow-Up Study - Habersaat, Stéphanie (Criminal justice and behavior, 2018)
The aim of this study was to investigate the sex-specific predictive value of age of onset of delinquent behaviors, callous-unemotional (CU) traits, and anger-irritability problems for externalizing behavior problems in institutionalized adolescents over the course of 1 year. A total of 118 girls and 240 boys from child welfare and juvenile justice institutions were evaluated twice: At T1, age of onset, CU traits, anger-irritability problems, nonverbal reasoning, and externalizing behavior problems were measured; at T2 (later), externalizing behavior problems were measured a second time. Results showed significant interactions between sex and anger-irritability problems, and between sex and CU traits, in the sense that the relation between these two predictors at T1 and externalizing behavior problems at T2 was stronger in girls than in boys. Results of this study point out sex differences in the validity of predictors of externalizing behavior problems.